2019
DOI: 10.1080/17483107.2019.1630018
|View full text |Cite
|
Sign up to set email alerts
|

Bimanual wheelchair propulsion by people with severe hemiparesis after stroke

Abstract: 250 word max) Aim: Individuals who require manual wheelchairs after stroke are typically taught to ambulate with compensatory propulsion (i.e. using their nonparetic arm and foot), risking disuse of the paretic arm. We investigated whether stroke survivors can instead ambulate in a bimanual, leverdriven wheelchair that requires the paretic arm to contribute half the propulsive input.Methods: Seventeen individuals with chronic stroke and severe hemiparesis (upper extremity Fugl-Meyer scores between 10 and 24) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…The device described here takes into account our experience developing and testing lever-drive wheelchairs for stroke rehabilitation [17]- [19]. We found that individuals with severe arm impairment in the chronic stage of stroke retain sufficient strength and coordination with their paretic arm to manoeuvre bimanual, lever-driven wheelchairs [17], [18]. Participants with stroke exhibited largely healthy biomechanics, with minimal shoulder hiking/leaning or trunk inclination.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The device described here takes into account our experience developing and testing lever-drive wheelchairs for stroke rehabilitation [17]- [19]. We found that individuals with severe arm impairment in the chronic stage of stroke retain sufficient strength and coordination with their paretic arm to manoeuvre bimanual, lever-driven wheelchairs [17], [18]. Participants with stroke exhibited largely healthy biomechanics, with minimal shoulder hiking/leaning or trunk inclination.…”
Section: Introductionmentioning
confidence: 99%
“…We modified this initial lever drive chair design with a hand clutching design to allow turning in place and backing up [17]. In a randomized control trial, we found that exercise with this device in the subacute phase of stroke led to a reduction in arm impairment compared to conventional treatment, demonstrating the therapeutic potential of wheelchair-based arm exercise after stroke [18]. However, therapists noted that the hand clutching technique required for overground propulsion placed a high cognitive demand on patients, and most struggled to learn to use the device for propulsion.…”
Section: Introductionmentioning
confidence: 99%
“…Wheelchairs propelled with levers used by both arms have the potential to offer both mobility and arm exercise. 8,9 Such devices could lead to a paradigm shift in wheelchair use in stroke rehabilitation. Currently, wheelchairs are used for ambulation after stroke, but are not typically thought of as a tool for exercise of the hemiparetic arm.…”
Section: Introductionmentioning
confidence: 99%
“…LARA (Lever-Actuated Rehabilitation and Ambulation) is a bimanual lever-driven wheelchair configured so that the paretic arm contributes to propulsion. 8,13 Pilot testing with a precursor device called RAE (the Resonating Arm Exerciser), which utilized the same lever configuration as LARA, showed that individuals with severe arm impairment in the chronic stage of stroke can pump a lever attached to the wheels of a wheelchair with their hemiparetic arm, rolling forward and backward, and that repeated pumping of these levers leads to therapeutic benefit. 14 We tested RAE in a home-based randomized control trial where independent training with RAE (~500 repetitions per hour) was found to be feasible and to significantly reduce arm impairment in individuals with chronic stroke, without increasing pain or tone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation